2018
DOI: 10.1016/j.ifacol.2018.08.211
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Risk Perception: Understanding the Gap Between Theory and Practice

Abstract: Abstract:The risks inherent in the supply chain threaten the effectiveness and the output of the chain. It is capable of hampering the growth and performance of organizations whose goods pass through a supply chain. This paper explores the awareness of supply chain risks of employees at different levels in a UK Agri-food industry, and the impact of these awareness on risk mitigation performance. Through literature review, this research identifies the main supply chain risks in the UK Agri-food industry, the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Ilhan and Rahim [9] indicate, among other activities in the process of digital transformation, the need for training employees as well as suppliers to successfully respond to new challenges. Adeseun et al [47] say procurement risks are more easily identified and managed when stakeholders are involved in the process and the consequences are clear. They also emphasized that there is a connection between employees' experience level and the organization itself.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Ilhan and Rahim [9] indicate, among other activities in the process of digital transformation, the need for training employees as well as suppliers to successfully respond to new challenges. Adeseun et al [47] say procurement risks are more easily identified and managed when stakeholders are involved in the process and the consequences are clear. They also emphasized that there is a connection between employees' experience level and the organization itself.…”
Section: Literature Overviewmentioning
confidence: 99%
“…There are several risks threatening supply chains, which can be segmented into several categories. The first one is that of risks related to human resources that have a direct impact on supply chains, such as the lack of qualified personnel [24], labor disputes and conflicts [25], disasters within the plant [26], theft [27], language and culture problem [1].The second category of risk is that related to end-customer such as inaccurate or variable sales and demand forecasts [28] and uncertainty of supply and demand [29] we can also find the category of risks related to customs such as import and export restrictions and tariffs [30]. The fourth category of risks is that of engineering and process risks, such as the risks related to the capacity [30] and deteriorated production performance [31].The fifth category of risks is related to financial and economic risks, we can mention for example, the impact of inflation and exchange rate changes [32], bankruptcy and insolvency of the supplier [1], cash-flow disruptions [33].…”
Section: Literature Review Supply Chain Risk Management and Risk Iden...mentioning
confidence: 99%
“…Traditional supply chain challenges have a direct impact on the SCRes enablers (shown in Figure 3), which requires the supply chain to manage changes and reduce disruptions. Traditional supply chains faced issues such as uncertainty, rising costs, inaccuracy, and increased risks (Abdel-Basset et al, 2018;Adeseun et al, 2018). Engineering and Operations Management Manila, Philippines, March 7-9, 2023 © IEOM Society International Although the approaches to both concepts (IoT and supply chain resilience) differ.…”
Section: Iot and Supply Chain Resilience Enablersmentioning
confidence: 99%